Finite Element Analysis of Mechanical Chair - Pandey, Nitesh; kumar, Manish; Srivastava, Amit Kumar; Gupta, Pankaj (Journal of Advanced Research in Mechanical Engineering and Technology, 2023)
This research explores the design of a steel chair addressing the crucial need for adaptability in modern living spaces. Advanced engineering techniques, specifically Finite Element Analysis (FEA), are employed to meticulously analyze and enhance the structural performance of this versatile furniture piece. The study focuses on simulating various scenarios using FEA to ensure that the chair meets stringent ergonomic standards, providing user safety and comfort in both seating and table configurations. The integration of transformative features, plays a pivotal role in refining the chair’s form through iterative processes based on predefined constraints. The paper systematically presents FEA findings, emphasizing stress distribution, displacement, and mass considerations within the chair’s structure. Simultaneously, visual insights into the chair’s design evolution through Generative Design offer a comprehensive understanding of its transformative journey.